From weed to medicinal plant: antioxidant capacities and phytochemicals of various extracts of Mikania micrantha - Ishak, Amirah Haziyah; Shafie, Nurul Husna; Mohd Esa, Norhaizan; Bahari, Hasnah; Ismail, Amin (Smith and Franklin Academic Publishing, 2018)
Mikania micrantha is commonly consumed as traditional medicine in some countries, including Malaysia. Little is known about the antioxidant properties and phytochemicals of M. micrantha. This study was aimed to investigate the total phenolic content (TPC), total flavonoid content (TFC) and antioxidant capacities of the leaves and stems of M. micrantha of hot water, cold water, 70% ethanol, ethyl acetate, and hexane extracts. Folin-Ciocalteu and aluminium chloride colorimetric assays were used to determine the TPC and TFC, respectively. The antioxidant capacities were determined using rapid, inexpensive and small-scale microplate of five different antioxidant assays. Gas chromatography-mass spectrometry (GC-MS) was used to chemically profile and characterize the phytochemicals. In comparison with different solvents, the ethyl acetate stems (EAS) and leaves (EAL) extracts of M. micrantha had the significantly greatest TPC (141±0.51 mg gallic acid equivalent/g) and TFC (70.1±0.92 catechin equivalent/g), respectively. Moreover, EAS extract had the significantly greatest antioxidant capacities using DPPH (EC50=324±61.4 μg/mL), ABTS (0.53±0.01 mmol trolox equivalent/g), FRAP (1.28±0.05 mmol Fe2+/g), phosphomolybdenum antioxidative power (219±7.03 mg ascorbic acid equivalent/g), and β-carotene bleaching (108±2.23%) assays. GC-MS analysis of EAS showed the presence of sesquiterpenes (30.46%), phenol (16.38%), and alkane hydrocarbons (10.45%), which may contribute to its antioxidant capacities. These findings suggest the stems extract of M. micrantha using ethyl acetate as the potential source of natural antioxidant agents and its utilization to prevent oxidative damage-related diseases could be further explored.